Relationship Of Knowledge With Pregnant Women's Attitude About Changes In Trimester I Psychology In The Work Area Of Kota Pinang Public Health Center, Labuhan Batu Selatan Regency In 2021 - Devi Sagita Saragi (Science Midwifery, 2022)
Pregnancy is an important phase in the life of a productive mother. During this period there will be many changes in the mother, both physically and psychologically. The influence of changes in the hormones estrogen and progesterone plays a role in emotional changes. This causes the mother to feel uncomfortable and triggers stress, which is characterized by the mother being often moody, anxious, restless, feeling uncertain, reduced concentration and often dizzy. In the early trimester of pregnancy, pregnant women are very sensitive and fragile, many fears that arise about the dangers that may occur to the mother and her baby. This is caused by lack of knowledge and attitudes. In this phase, pregnant women need advice, encouragement, direction and help from the people around them. This study aims to determine the relationship between knowledge and attitudes of pregnant women about psychological changes in the first trimester in the Work Area of the Pinang City Health Center, Labuhan Batu Selatan Regency in 2021.This type of research is an analytic survey with a cross sectional design.The research is located at the Kota Pinang Health Center, Labuhan Batu Selatan Regency. The population of the study, namely all pregnant women in the first trimester, amounted to 108 people. The sample size is 52 people. Data were analyzed by chi-square test. The result of this research is that there is a relationship between knowledge and attitudes of pregnant women about psychological changes in the first trimester (p-value 0.006). The conclusion is that there is a significant relationship between knowledge and attitudes of pregnant women about psychological changes in the first trimester at the Puskesmas Kota Pinang, Labuhan Batu Selatan Regency. It is recommended that pregnant women increase their knowledge and actively seek various information, especially psychological changes in the first trimester.